Parasitic Wasps Can Reduce Mortality of Teosinte Plants Infested With Fall Armyworm: Support for a Defensive Function of Herbivore-Induced Plant Volatiles - de Lange, Elvira S.; Farnier, Kevin; Degen, Thomas; Gaudillat, Benjamin; Aguilar-Romero, Rafael; Bahena-Juárez, Fernando; Oyama, Ken; Turlings, Ted C. J. (Frontiers in Ecology and Evolution, 2018)
Many parasitic wasps use volatiles emitted by plants under herbivore attack to find their hosts. It has therefore been proposed that these inducible plant volatiles serve an indirect defense function by recruiting parasitoids and other natural enemies. This suggested function remains controversial because there is little evidence that, in terms of fitness, plants benefit from the actions of natural enemies, particularly parasitoids, which do not immediately kill their hosts. We aimed to address this controversy in a semi-natural field experiment in Mexico, where we used large screen tents to evaluate how parasitoids can affect plant performance. The tritrophic study system comprised teosinte (Zea spp.), the ancestor of maize, Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) and Campoletis sonorensis Cameron (Hymenoptera: Ichneumonidae), which have a long evolutionary history together. In tents without parasitoids, S. frugiperda larvae inflicted severe damage to the plants, whereas in the presence of parasitoid wasps, leaf damage was reduced by as much as 80%. Parasitoids also mitigated herbivore-mediated mortality among young teosinte plants. Although these findings will not resolve the long-standing debate on the adaptive function of herbivore-induced plant volatiles, they do present strong support for the hypothesis that plants can benefit from the presence of parasitoid natural enemies of their herbivores.